2021
DOI: 10.1111/jhn.12840
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient dietary intakes and their food sources in adults: the Hellenic National Nutrition and Health Survey (HNNHS)

Abstract: Background: The present study aimed to assess micronutrient intake among Greek adults and to identify the main food sources that contribute to it. Methods: Food consumption data from 2389 participants in the Hellenic National Nutrition and Health Survey (HNNHS), collected with 24-h recalls, was used to calculate micronutrient intakes. Usual nutrient intake was estimated according to the National Cancer Institute method. Nutrient adequacy was estimated using the estimated average requirement (EAR) cut-point met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, it has been reported that overconsumption of foods high in simple sugars replace more nutrient dense foods, and result in nutrient inadequacies [9,37]. This may be the case among children and adolescents in Greece based on a previous study reporting that most vitamins and essential minerals were derived from low-quality foods [46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that overconsumption of foods high in simple sugars replace more nutrient dense foods, and result in nutrient inadequacies [9,37]. This may be the case among children and adolescents in Greece based on a previous study reporting that most vitamins and essential minerals were derived from low-quality foods [46].…”
Section: Discussionmentioning
confidence: 99%
“…Reports from national consumption surveys providing estimates of selenium intake from foods and fortified foods (excluding food supplements) are available for 10 countries: Denmark, Estonia, Finland, France, Greece, Lithuania, Norway, Spain, Sweden, the Netherlands (Pedersen et AECOSAN, 2017;Anses, 2017;Hansen et al, 2017;Lemming et al, 2018;Valsta et al, 2018;Mitsopoulou et al, 2020;van Rossum et al, 2020;Bulotaitė et al, 2021;Kukk et al, 2021;Mitsopoulou et al, 2021). At the P95, the estimated intakes are up to 80.9 μg/day in male infants (aged ≥ 3 to < 12 months; 3 countries), up to 108.6 μg/day in female toddlers (1 to < 3 years; 5 countries), up to 153.3 μg/day in male other children (3 to < 10 years; 5 countries), up to 183.7 μg/day in female adolescents (10 to < 18 years; 6 countries) and up to 227.7 μg/day in male adults (≥ 18 years; 6 countries).…”
Section: Intake Estimates From National Consumption Surveysmentioning
confidence: 99%
“…Kimchi only contributes to a small proportion of the total sodium intake of the Korean diet although our results present that higher kimchi consumption is associated with higher sodium intake 49. Moreover, the main vegetables of kimchi, such as cabbage and radish, are dietary sources of potassium, and individuals who consume higher amounts of sodium might benefit from increasing potassium intakes to counteract the effect of sodium 50 51…”
Section: Discussionmentioning
confidence: 62%